"After the Humidity and Stillness of Yesterday . . .": Drifting, Reading, Writing Self and Others, Traveling in Otherwhens and Otherwheres. (April 2017) - Gannon, Susanne
This article turns to a handwritten travel journal from more than two decades ago to explore how the past might be animated in the present through provoking affective, material and imaginative encounters with the text, the subject, and the world. This experimental animation of space-time through writing draws upon the figure of the mirror in Foucault's "heterotopias" as it sets in motion lines of force and displacement that enable openings toward emerging intercorporeal subjects in writing.